ANALISIS PERMINTAAN REKREASI DAN STRATEGI PENGEMBANGAN WISATA BAHARI DI KAWASAN WISATA LAGOI, KECAMATAN TELUK SEBONG, KABUPATEN BINTAN - Tince Sofyani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
The aims of the research are : 1). to measure both the potential andfeasibility of marine tourism development at Lagoi area tourism , 2). to identifythe characteristic and preferences of tourist at Lagoi area tourism 3). to find thedemand curve of tourist against recreation of marine tourism at Lagoi areatourism, and 4) to determine the strategic for marine tourism development atLagoi area tourism.The number of respondents is 40 deriving from domestic tourist. The datawere then analyzed by using linear regression analysis with model of travel costmethod and also SWOT analysis.The results of assessment the potential of Lagoi area tourism that locationwas suitable for recreation because the nature of beautifulness of the beach andproper to development. Demand curve depicted to follow constant elasticitymodel with price elasticity value equal to – 0,8823, meaning all changes intraveling expense equal to 1 %, hence mount tourist visit will change equal 0,8823% Result from SWOT analysis is support aggressive development policy.